A first-principles study on the phase stability and physical properties of a B-site ordered Nd2CrFeO6 double perovskite. Issue 3 (23rd December 2021) - Bhuyan, M. D. I.; Hossain, Rana; Ara, Ferdous; Basith, M. A.
Abstract : B-site ordered Nd2 CrFeO6 double perovskite: A thermodynamically stable ferrimagnetic semiconductor with a band gap in the visible range predicted by DFT calculations. Abstract : Here, the first-principles predictions on the structural stability, magnetic behavior and electronic structure of B-site ordered double perovskite Nd2 CrFeO6 have been reported. Initially, the ground state of the parent single perovskites NdCrO3 and NdFeO3 has been studied to determine the relevant Hubbard U parameter to investigate the properties of Nd2 CrFeO6 . The thermodynamic, mechanical, and dynamic stability analyses suggest the possibility of the synthesis of the Nd2 CrFeO6 double perovskite at ambient pressure. The compound shows a ferrimagnetic nature with 2 μ B net magnetic moment and the magnetic ordering temperature has been estimated to be ∼265 K. The electronic structure indicates a higher probability of direct photon transition over the indirect transition with a band gap of ∼1.85 eV. Additional effects of Nd (4f) spin and spin–orbit coupling on the band edges have been found to be negligible for this 4f–3d–3d spin system. This first-principles investigation predicts that due to the ferrimagnetic nature and a significantly lower band gap compared to those of its antiferromagnetic parent single perovskites, the B-site ordered Nd2 CrFeO6 double perovskite could be a promising material for spintronic and visible-light driven energy applications.